Investigating the Influence of Shariah Compliance on the Level of Currency Exposure Across Time Scales: An Application of Wavelet Approach (MATEMATIKA, 2021)
Currency exposure is defined as the risk where firm value is sensitive to changes in foreign exchange movement. Several studies have been devoted to measure the extent of foreign exchange exposure of Malaysian corporations. However, previous efforts have ignored the potential of Shariah compliance and time scale effects on the measurement. Motivated from these specification problems, the study investigated the influence of Shariah compliance on the level of multi-scale exchange rate exposure using the Maximal Overlap Discrete Wavelet Transformation (MODWT) approach. The study focused on a sample of 12 Shariah compliant firms (SCF) and 12 non-Shariah compliant firms (NSCF) listed under the Food and Beverage industry in Malaysia from July 2005 till August 2018. As a result, the study found that the level of Shariah compliance had a negligible impact on the level of exchange exposure. The study also found that the level of currency exposure increased from low to high time scale, indicating that widened investment intervals entail greater exchange risk for both SCF and NSCF. In terms of policy implication, the study infers that the SCF and NSCF share almost identical exchange risk profiles which uphold the law of one price. In fact, there is no basis to expect different risk management routines in dealing with exchange risk between the two groups. However, the study stresses the importance of incorporating the time scale factor in managing exchange risk for both groups.